Plant growth and phenolic compounds in the rhizosphere soil of wild oat (Avena fatua L.) - Iannucci, Anna; Fragasso, Mariagiovanna; Platani, Cristiano; Papa, Roberto (Frontiers in Plant Science, 2013)
The objectives of this study were to determine the pattern of dry matter (DM) accumulation and the evolution of phenolic compounds in the rhizosphere soil from tillering to the ripe seed stages of wild oat (Avena fatua L.), a widespread annual grassy weed. Plants were grown under controlled conditions and harvested 13 times during the growing season. At each harvest, shoot and root DM and phenolic compounds in the rhizosphere soil were determined. The maximum DM production (12.6 g/plant) was recorded at 122 days after sowing (DAS; kernel hard stage). The increase in total aerial DM with age coincided with reductions in the leaf/stem and source/sink ratios, and an increase in the shoot/root ratio. HPLC analysis shows production of seven phenolic compounds in the rhizosphere soil of wild oat, in order of their decreasing levels: syringic acid, vanillin, 4-hydroxybenzoic acid, syringaldehyde, ferulic acid, p-cumaric acid and vanillic acid. The seasonal distribution for the total phenolic compounds showed two peaks of maximum concentrations, at the stem elongation stage (0.71 μg/kg; 82 DAS) and at the heading stage (0.70 μg/kg; 98 DAS). Thus wild oat roots exude allelopathic compounds, and the levels of these phenolics in the rhizosphere soil vary according to plant maturity.